Efektivitas Program Keluarga Harapan Bagi Keluarga Penerima Manfaat: Studi Kasus Kecamatan Tanjungpinang Timur Kota Tanjungpinang - Rosnita Rosnita; Hernita Lidia Bonte (Universitas 17 Agustus 1945 Semarang, 2024)
The government makes a program with the aim of prospering the community, one of these programs is the Family Hope Program, where the community receiving the assistance is called KPM, this study aims to answer about the effectiveness of the family hope program that has been made by the government, especially in East Tanjungpinang District. The research method uses a descriptive method with a qualitative approach, using the theory put forward by Sutrisno (2010) which includes program understanding, target accuracy, timeliness, achievement of goals and real changes. The results of the research on the effectiveness of the Family Hope Program for Beneficiary Families in the East Tanjungpinang District of Tanjungpinang City seen from the target of the program policy are correct in accordance with the regulations made, because they follow the DTKS which will be identified in accordance with the data submitted, the timing of the implementation of PKH assistance has indeed been determined by the central government, when it will be disbursed, but overall it can be said that the timeliness of the distribution of assistance has not been maximized, because sometimes the assistance disbursed by the government can advance from the date set by the government. The overall goal of the program to improve the welfare of KPM can be said to be ineffective because the achievement of numbers in 2023 can be said to have not been achieved. Because it is seen from the direct field that there are still many people who need assistance, and most likely if it is recorded in detail, it falls into the category of those entitled as KPM participants, seen from the real changes provided by the program, it has not been optimal, but it has been enough to help the KPM community with the assistance provided, it can be seen that there are several communities as KPM who are able to manage the assistance provided by PKH for entrepreneurship. The suggestions that can be submitted are, the government, especially the East Tanjungpinang District government and PKH supervisors to continue to strive to advance the community.